Sustainability of Sculpture and Monument in the Built Environment - Uzzi, Festus Osarumwense; Omolola, Feyisara Sunday; Afeez, Siyanbola Babatunde; Odewole, Peter Oluwagbenga (NIU Journal of Social Sciences; Vol 8 No 1 (2022): NIU Journal of Social Sciences, Vol. 8 No. 1, March 2022DO - 10.58709/niujss.v8i1.1431, 2022)
Sculptural monument has been described as an exhibition of works of the visual arts or practices not displayed in galleries and museums but featured or performed in streets, city squares or public spaces and accessible to the public. therefore, this paper documents the sustainability of sculpture/monument in the built environment an illustrated step-by-step approach in the designing, Sculptural monuments are three-dimensional visual art forms that are executed through varying techniques and materials as memorial or funerary monuments, the materials for representation are usually solid in form in view of the purpose and the period they are to serve. It was observed that good management of any public utility would not only ensure its accessibility to the teaming public, but its sustainability will further ensure the longevity This study reveals that public sculpture has played significant role of beautifying the built environment, it also provides the social function of education, information and enhancing social order by preserving the cultural history of the people the past and at contemporary times in societies Keywords: Sculptural Monument, execution, cultural values, aesthetics and Environment.